An energy-efficient point-coverage-aware clustering protocol in wireless sensor networks. (2018) - Nguyen, Tri Gia; So-In, Chakchai
Preserving coverage is one of the most essential functions to guarantee quality of service in wireless sensor networks. With this key constraint, the energy consumption of the sensors including their transmission behaviour is a challenging problem in term of how to efficiently use them while achieving good coverage performance. This research proposes a clustering protocol, point-coverage-aware (PCACP), based on point-coverage awareness with energy optimisations that focuses on a holistic view with respect to activation sensors, network clustering and multi-hop communication, to improve energy efficiency, i.e., network lifetime extension while preserving coverage and maximising the network coverage. The simulation results demonstrate the effectiveness of PCACP, which strongly improves the performance. Given a diversity of deployments with scalability concerns, PCACP outperformed other competitive protocols, i.e., low energy adaptive clustering hierarchy (LEACH), coverage-preserving clustering protocol (CPCP), energy-aware distributed clustering (EADC) and energy and coverage-aware distributed clustering (ECDC) in terms of conserving energy, sensing point coverage ratios and overall network lifetime.